ANALISIS HASIL BELAJAR MAHASISWA SECARA LURING DAN DARING MATA KULIAH STATISTIK EKONOMI I STIE DHARMA BUMIPUTERA JAKARTA - Nurhanan, Nurhanan (JURNAL ILMIAH EDUNOMIKA, 2025)
The aim of this research is to find out whether there is a significant difference in the results of offline and online student lectures for the Economic Statistics I course at STIE Dharma Bumiputera Jakarta. The research method used is a quantitative research method by conducting hypothesis testing in the form of a Paired Sample t-Test. The data used is secondary data in the form of data from offline and online lectures in the even semester of the 2023/2024 academic year which is documented on the STIE Dharma Bumiutera ecampuz. By using a data processing tool in the form of SPSS version 22, the results were obtained that offline lectures were better than online lectures.